Postmortem Racialization: Reconceptualizing Frantz Fanon’s Black Subject - Cunningham, Andreana (Transforming anthropology, 2024)
This article proposes a theoretical model that elucidates the positionality of the skeletal remains of Afro-descendants, or Black postmortem subjects. Anonymous burials or displaced material remains are a persistent and salient feature of Black burial grounds, indicating their conception as not being worthy of sustained investment and care. This article reviews and draws from the work of Frantz Fanon, whose theories of alienation and spatial compartmentalization provide a framework by which to articulate a process of displacement and the strategies used to constrain their designated status. The article uses these theories to construct a theoretical model that describes the initial and repeated encounters that occur between the living and Black postmortem subjects that have direct consequences for their placement.